Periodontal disease in pregnancy: A comparative prospective study - Ortmann, Nora; Möllers, Mareike; Braun, Janina; Sourouni, Marina; Willy, Daniela; Köster, Helen Ann; Klockenbusch, Walter; Schmitz, Ralf; Oelmeier, Kathrin (Zeitschrift für Geburtshilfe und Neonatologie, 2023)
Introduction Periodontal disease affects many pregnant women and may be associated with adverse pregnancy outcomes. The object of this study was to evaluate women’s level of knowledge about this condition in pregnancy. We compared level of knowledge, participation in medical screening, and periodontal health status in pregnant women and nonpregnant controls.Material and Methods This study included 141 pregnant and 141 nonpregnant women, examined by one examiner at the Department of Gynecology and Obstetrics of the University Hospital Muenster, Germany. With reference to periodontal health status, the Periodontal Screening Index was used and a questionnaire was designed to represent the level of knowledge and predisposing factors.Results Pregnant women showed a strong tendency towards higher Periodontal Screening Indices than the nonpregnant controls (P=0.058). A strong positive correlation between participation in screenings and a lower Periodontal Screening Index was measured, but no direct relation between knowledge and periodontal health was detected. However, a better level of knowledge correlated noticeably with participation in screening programs. Educational attainment was found to be a main factor correlated with periodontal health and further factors such as medical screening and smoking habits. A great number of women felt they were not sufficiently informed about oral health aspects in pregnancy.Conclusions As participation in screenings was a main item that positively correlated with healthier periodontal status, it had to be a focused element. The possible positive influence of knowledge regarding the participation in screening programs showed not only the need to spread awareness but also the need for proper education.
Keywords: evidence based antenatal care; maternal risks; prevention; oral health; periodontitis